2022
DOI: 10.1017/s0029665122002683
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in older persons: the role of nutrition

Abstract: Fatigue is defined as a symptom leading to the inability to continue functioning at the expected activity level. It is a highly prevalent symptom, challenging to frame into monodimensional pathophysiological mechanisms. As a result, fatigue is often underestimated in the clinical setting and is wrongly considered an unavoidable consequence of ageing. Several potential mechanisms responsible for fatigue have been proposed, including sleep patterns, autonomic nervous system abnormalities and biological complexit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Fatigue can be described as a symptom of malnutrition and frailty. 33 Fatigue is closely related to adverse outcomes, significantly increasing medical costs and reducing the quality of life. 16 34 A recent systematic review classified fatigue-related factors into four aspects: biological, behavioural, psychological and social levels, and poor nutritional status was included in the behavioural levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue can be described as a symptom of malnutrition and frailty. 33 Fatigue is closely related to adverse outcomes, significantly increasing medical costs and reducing the quality of life. 16 34 A recent systematic review classified fatigue-related factors into four aspects: biological, behavioural, psychological and social levels, and poor nutritional status was included in the behavioural levels.…”
Section: Discussionmentioning
confidence: 99%
“… 39 40 Fatigue management strategies include strengthening physical activity, improving sleep and nutritional support to compensate for inadequate energy and protein intake to meet an individual’s specific needs that may help combat fatigue. 33 41 …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all these mechanisms are also observed in the context of COVID-19 [ 29 ]. Fatigue may therefore be envisioned as a clinical indicator of an underlying biological abnormality [ 30 , 31 ]. However, the subjectivity of the symptom and the lack of a gold standard measure for fatigue assessment contribute to its poor consideration in the clinical practice [ 29 ].…”
Section: Psycho–social Impactmentioning
confidence: 99%
“…In both approaches, the operationalization of fatigue measurement has not been clearly defined and varies widely across the literature, including subjective symptoms related to fatigue (exhaustion, anergia, etc. ), further contributing to poor clinical consensus 6–9 . A systematic review of 158 frailty scales identified 120 unique fatigue items 10 .…”
Section: Introductionmentioning
confidence: 99%
“…), further contributing to poor clinical consensus. [6][7][8][9] A systematic review of 158 frailty scales identified 120 unique fatigue items. 10 Although fatigue has a variety of etiologies and mechanistic pathways, the heterogeneity further complicates research on fatigue as a frailty component.…”
Section: Introductionmentioning
confidence: 99%